Long-term air pollution exposures on type 2 diabetes prevalence and medication use - Ying-Ying Meng; Yu Yu; Susan H. Babey; Jason Su (Elsevier, 2023)
Background: Type 2 diabetes has raised great public health concerns due to its association with the increased risk of several adverse health outcomes. We aimed to investigate the association of criteria air pollutants and traffic density with the prevalence of type 2 diabetes and antidiabetic medication use in California. Methods: A cross-sectional study was conducted using 2005 California Health Interview Survey (CHIS) data, linked with criteria air pollutant exposure measures, including government-monitored ozone (O3), particulate matter (PM10, PM2.5) and nitrogen dioxide (NO2), residential traffic density, and land use regression modeled NOX, NO, and NO2 estimates for Los Angeles County only based on the respondents' geocoded residential addresses. Weighted logistic regression models were used to examine the influences of 36-month average exposures to each air pollutant and traffic density on diabetes prevalence and medication use. Results: Among 31,483 CHIS 2005 state-wide respondents, 6.7% of adults reported having been diagnosed with type 2 diabetes. We observed type 2 diabetes prevalence was positively associated with exposures to O3, PM10, and PM2.5, and with NO, NO2, and NOx only in Los Angeles County. For each 10ppb increase in O3 or 10ug/m3 increase in PM10 or PM2.5, the odds of taking any medication increased by 40%, 56%, and 50%; taking pills increased by 33%, 31%, and 41%; taking insulin increased by 43%, 53%, and 46%; and taking both insulin and pills increased by 70%, 60%, and 88%, respectively. When traffic density within 750 feet of a respondent's home increased by one interquartile, 7% increase in odds of using any medication and taking pills was also observed. Conclusion: This study adds to evidence indicating greater air pollution exposure is associated with increased diabetes prevalence. It also provides new evidence demonstrating a strong association between pollutant exposure and antidiabetic medication use in adult Californians.